Early life history stages of family Centrolophidae in the eastern Adriatic - Dulčić, Jakov (Annales. Series historia naturalis, 1999)
Use of early life history stages of fish in systematic and ecological studies has increased in recent years. It is now recognized that eggs, larvae and juveniles present a wide array of characters that are largely independent of adult characters and suitable for a systematic analysis. Fisheries recruitment studies focus on the survival of eggs and larvae as the most important factor influencing variations in population abundance. A requisite to these studies is detailed information on the appearance of fish eggs and larvae in order to identify them in plankton samples ...
Keywords: Centrolophidae; razvoj; ribe; vzhodni Jadran